Studi Deskriptif Peran Guru Sebagai Pendidik dalam Mengembangkan Karakter Disiplin Siswa di Kelas IV A SD Negeri 01 Kota Bengkulu - Meivia Anggela; Osa Juarsa; Bambang Parmadi (Universitas Bengkulu, 2020)
This study aims to describe the role of teachers as educators in developing the discipline character of students in class IV A 01 Kota Bengkulu Elementary School. This type of research is qualitative research, with descriptive research methods. The subjects of the study were the principal, grade IV A teachers, and grade IV A students. Data collection techniques used observation, interviews, and documentation. Data analysis was performed by data collection, data condensation, data presentation, and drawing conclusions. Testing the validity of the data using extended observations, increasing perseverance and triangulation. The results of this study indicate that the role of the teacher as an educator in developing the character of student discipline has been carried out in class IV A. The role of the teacher in developing the character of student discipline consists of as motivators, facilitators and evaluators. As a motivator the teacher has given encouragement to students to always be disciplined in the classroom, as a facilitator the teacher has provided the facilities needed by students to develop the character of their discipline and as an evaluator the teacher has also conducted an evaluation to see the extent of the development of the discipline character of students in the class.